2009
DOI: 10.1063/1.3254372
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamical effects in liquid water: A semiclassical study on the diffusion and the infrared absorption spectrum

Abstract: The important role of liquid water in many areas of science from chemistry, physics, biology, geology to climate research, etc., has motivated numerous theoretical studies of its structure and dynamics. The significance of quantum effects on the properties of water, however, has not yet been fully resolved. In this paper we focus on quantum dynamical effects in liquid water based on the linearized semiclassical initial value representation (LSC-IVR) with a quantum version of the simple point charge/flexible (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 133 publications
2
84
2
1
Order By: Relevance
“…Therefore, in applications in the condensed phase ZPE is ignored and instead a purely classical phase space sampling is done. However, several applications have demonstrated the importance of ZPE in MD calculations, thus the absence of the ZPE in the standard classical MD is a significant issue [6][7][8][9][10]. Indeed, in gasphase reaction dynamics calculations the quasiclassical trajectory (QCT) method is frequently used, in which the reactants have ZPE.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in applications in the condensed phase ZPE is ignored and instead a purely classical phase space sampling is done. However, several applications have demonstrated the importance of ZPE in MD calculations, thus the absence of the ZPE in the standard classical MD is a significant issue [6][7][8][9][10]. Indeed, in gasphase reaction dynamics calculations the quasiclassical trajectory (QCT) method is frequently used, in which the reactants have ZPE.…”
Section: Introductionmentioning
confidence: 99%
“…But there are plenty of cases, e.g. the spectrum of liquid water, [3][4][5] hydrogen-diffusion on metals, 6,7 and proton/hydride-transfer reactions, [8][9][10][11][12][13] for which one needs to evaluate time-correlation functions of the form 1 Z C AB (t) = 1…”
Section: Introductionmentioning
confidence: 99%
“…für Physikalische Chemie, ETH Zürich, CH-8093 Zürich, Switzerland b) Corresponding author: sca10@cam.ac.uk approximation), 3,[15][16][17][18][19][20][21][22][23][24][25][26][27] in which the quantum Liouvillian is expanded as a power series in 2 , then truncated at 0 . Miller 15,16 and later Shi and Geva 17 showed that this approximation is equivalent to linearizing the displacement between forward and backward Feynman paths in the exact quantum time-propagation, which removes the coherences, thus making the dynamics classical.…”
Section: Introductionmentioning
confidence: 99%
“…41,[68][69][70] The PI-ST representation of the Boltzmann operator can be substituted in the expression for the TCF in Eq. (40) to obtain…”
Section: B Linearized Ivr (Lsc-ivr)mentioning
confidence: 99%